Antifungal Potential of Aquous Extract of Some Medicinal Plants Against Onychomycosis-Causing Agents in Skikda Region/North-Eastern of Algeria - Ennaghra, Nadjet; Boudjellab, Zine Eddine; Ghannem, Maya; Bourzama, Ghania; Bououza, Fatiha; Aouzal, Badis; Soumati, Boudjemaa; Bounhilet, Wided; Boudjbiba, Djaballah Hana; Ramdan, Asma; Еннагра, Наджет; Буджеллаб, Зін Еддін; et al. (PH "Akademperiodyka" of the NAS of Ukraine, 2025)
Onychomycosis is a common fungal infection. This study, carried out in the Skikda region, North-Eastern Algeria, in February 2020, aims to evaluate three medicinal plants potential effects as antifungal agents, namely Zingiber officinale, Piper nigrum, and Syzygium aromaticum, on the growth of three fungal isolates: Aspergillus sp., Alternaria sp., and Fusarium sp. isolated from individuals diagnosed by onychomycosis infection in the Skikda region, North-Eastern Algeria. Methods. The antifungal activity of the plant aqueous extracts was assessed using the diffusion technique on Sabouraud. Results. Data show that Aspergillus sp. is the most frequent with 29.70%, followed by Fusarium sp and Alternaria sp., with a frequency of 21.6%. Onychomycosis mainly affects females with 61.29%, predominating in the age group of 30  to 40. Also, Zingiberofficinale's extract was the most effective, with 100% mycelial growth inhibition (MGI) at 20 % (V/V) concentration for each of the three tested fungal species. Then, at a concentration of 20 % (V/V), Syzygium aromaticum extract showed an average MGI% of 100%, 100%, and 60.56% from Fusarium sp., Alternaria sp., and Aspergillus sp., respectively. Finally, at a concentration of 20 % (V/V), Piper nigrum’s  extract had an average MGI% of 83.15%, 81.29%, and 100% against Fusarium sp., Aspergillus sp., and Alternaria sp. respectively. Conclusions. Findings suggest that Alternaria sp. is the most fungal species susceptible to the three tested extracts, followed by Fusarium sp. and Aspergillus sp. These findings confirm the potential therapeutic effects of those medicinal plants in combating fungal diseases and bring up interesting possibilities for developing new natural medicines.